(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
Participation of the widespread pleurocarpes moss Hypnales order of bryocommunities formation is analized. It is found out that 64,1 % found out epiphytes and epixiles communities the probed species are prevail and they are the diagnostic types of associations, and the coenotic participation of 24,4 % communities is insignificant. The classes of constancy of probed spiecies are lov enough: for Hypnum pallescens Hedw. P. Beauv., – III, Platygyrium repens (Brid.) Shimp., Pylaisia polyanthа (Hedw.) Schimp, The result of briocommunities classification accordingly ecologo-floristic classification (after Braun-Blanke method and its characteristics are resulted at this report. The association Ptilidio pulcherimi-Hypnetum pallentis Barkm. ex Wilm. 1962 and its phytocenotic description is give for Ukraine at first.